"If only they forgot that I was Syrian and an Arab, I am a human beings too." Syrian university students' experiences of being a foreigner: A phenomenological study. (July 2021) - Kaya, Yunus
Abstract: Migration is voluntary or forced relocation of individuals from a familiar physical, social, and cultural environment to an unfamiliar one. While migration is a challenging experience, traumatic experiences that happened before and after migrating may have numerous adverse effects. The aim of this study was to evaluate Syrian nursing students' experiences of being a foreigner before and after migration and throughout their university lives. Phenomenology, which is a qualitative research design, was used in this study. The study was conducted with 16 Syrian university students' in Turkey. Data was collected through semi-structured, face-to-face, in-depth interviews. Data was analyzed using interpretive phenomenological analysis, which yielded four main themes and 19 subthemes. The four themes were traumatic experiences that caused them to migrate, problems after migrating, being a foreigner at a Turkish university, and psychological issues. The results show that migration has numerous physical, social, cultural, and mental effects on human lives.